Settlement of Inheritance Property Distribution Through Consensus in the Perspective of Islamic Law - Lestari, Maylyndha Marlina (IJoIS: Indonesian Journal of Islamic Studies, 2025)
The division of inheritance is the transfer of ownership rights of the inherited property to the heirs. A deliberative division of inheritance can help minimize disputes between heirs. Some steps that can be taken in completing the division of inheritance are: agreeing on the inheritance law to be used, determining the inheritance of the testator, determining the heirs, calculating the share of the heirs, making an agreement on the division of inheritance. This paper explains the importance of understanding the division of inheritance by deliberation in a fair community environment. The presentation of this paper is based on the analysis of library data with a descriptive model. From the results of the discussion, it can be concluded that the settlement of the division of inheritance through deliberation consensus in the perspective of Islamic law is carried out by deliberation consensus, namely by sitting together to solve a problem by presenting all heirs, religious leaders, government officials and families who are close to the heirs and heirs. This deliberative division is due to several factors, namely social factors where this division can reduce conflicts between heirs. In the perspective of Islamic law, this practice is the division of inheritance based on mutual agreement of the heirs. This division is carried out after the heirs realize their respective shares. The division of inheritance by deliberation is regulated in Article 183 of the Compilation of Islamic Law.